2018
DOI: 10.15578/ifrj.23.2.2017.89-96
|View full text |Cite
|
Sign up to set email alerts
|

GENETIC DIVERSITY OF MACKEREL SCADS, Decapterus macarellus (Cuvier, 1833) IN THE INDIAN OCEAN

Abstract: Mackerel scads (Decapterus macarellus) is a small widely distributed pelagic species in ocean. In 2013, monthly catch and abundance index of mackerel scads increased in western part of Sumatera waters. High exploitation of mackerel scads may lead to decrease stock due to the over exploitation. Stock information is very useful for calculating of the potential fish. Genetic analysis is one of the powerful tools to estimate fish stock quickly. Genetic diversity of mackerel scads in this study was analyzed using R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Comparison of size ranges of mackerel scad caught in Dorery Bay based on the present research with several previous studies in variousl regions is presented in Table 1. It showed that the average length interval of D. macerellus was smaller than that taken in the Celebes Sea and also smaller than the size at first maturity (Lm), namely 26.89 cm [15].…”
Section: Fish Size Distributionmentioning
confidence: 89%
See 1 more Smart Citation
“…Comparison of size ranges of mackerel scad caught in Dorery Bay based on the present research with several previous studies in variousl regions is presented in Table 1. It showed that the average length interval of D. macerellus was smaller than that taken in the Celebes Sea and also smaller than the size at first maturity (Lm), namely 26.89 cm [15].…”
Section: Fish Size Distributionmentioning
confidence: 89%
“…Other aspects related to the level of fish utilization have also been widely reported, with various approaches such as production models based on the fish catch [10,11] and based on the length of fish life [12,13]. Further, studies on stock identification are especially about morphometry, otolith measurements [14], and stock potential estimation [15].…”
Section: Introductionmentioning
confidence: 99%